Principles of Spread-Spectrum Communication Systems - Torrieri, Don.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This textbook, now in its 5th edition, provides updated state-of-the-art coverage of spread-spectrum communication systems with new applications throughout the book. In this edition, the author extends sections with more comprehensive details about many topics. Some of the more complex sections have been rewritten to make them easier to understand. New subsections, sections, figures, and problems have been added throughout the book. New or expanded topics include frequency-hopping systems with multisymbol CPFSK detection, derivations of spread-spectrum systems with differential data modulations, chaotic systems, channel-state information, and MIMO. As with previous edition, the author presents mathematical analyses of spread-spectrum systems that provide insights into their operations and limitations and are of theoretical and practical interest to both researchers and system designers. He includes updated problems at the end of each chapter, which are intended to assist readers in consolidating their knowledge and to give practice in analytical techniques. Eight appendices provide the mathematical tools that are useful in understanding the main text. Fully revised 5th edition presents a comprehensive treatment of spread-spectrum communication systems; Features new or expanded material such as frequency-hopping systems with multisymbol CPFSK detection, derivations of spread-spectrum systems with differential data modulations, chaotic systems, channel-state information, and MIMO; Includes a full suite of classroom materials including problems, examples, and mathematical appendices; Request lecturer material: sn.pub/ lecturer-material.
Introduction -- Channel Codes and Modulation -- Direct-Sequence Systems -- Frequency-Hopping Systems -- Code Synchronization -- Adaptive Filters and Arrays -- Fading and Diversity -- Code-Division Multiple Access -- Mobile Ad Hoc and Cellular Networks -- Iterative Channel Estimation, Demodulation, and Decoding -- Detection of Spread-Spectrum Signals -- Conclusion.
Keywords: Telecommunication; Database management; Signal processing; Communications Engineering, Networks; Database Management System; Signal, Speech and Image Processing .; Spread spectrum communications